Polysaccharide-specific B cell responses to vaccination in humans. - Mitchell, R; Kelly, D; Pollard, A; Trück, J (Landes Bioscience, 2014)
The introduction of vaccines containing the capsular polysaccharides of N. meningitidis, S. pneumonia, and H. influenzae type b has driven a significant reduction in cases of disease caused by these bacteria. The polysaccharide-specific antibody responses following vaccination are well characterized, however less is known about the B cells underlying this response. Here, we summarize the plasma cell (PC) and memory B cell (BMEM) responses following plain polysaccharide and protein-polysaccharide conjugate vaccination, drawing together studies covering a range of vaccines and age groups. These studies show that infant primary PC and BMEM responses to polysaccharide-conjugate vaccines are low in relation to older age groups but are significantly higher following booster doses. PC kinetics have generally been found to follow a similar pattern irrespective of vaccine type or age group, whereas divergent BMEM responses have been reported following plain polysaccharide and conjugate vaccination. A degree of correlation between early BMEM responses and maintenance of protective antibody levels has been identified in some studies, but the relationship between the 2 remains unclear. Identification of the B cell subsets involved and the mechanisms by which they are induced may provide a better understanding of the role of B cells in maintaining protective immunity through vaccination.